(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Imagine that suppose your children fell into a bore well nearby your home place how do you feel a feeling came to my mind. When I go home I saw news in the Television Channel one boy fell in the bore well. From the past 10 years I am hearing this news in TV channels. 99% people also I found dead while I thought that why it is happening I found a problem which is the starting point of my research.